PERSEPSI GURU SD TERHADAP PENGGUNAAN MEDIA KONKRET DALAM PEMBELAJARAN KALIMAT MATEMATIKA BILANGAN CACAH DI KELAS III - Azlia Putri Amanda; Hafiziani Eka Putri; Diana Bachtiani Agustin; Fiska Nurasyifa; Indriani Putri Wijaya; Mochammad Salman Haidar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mathematics learning at the elementary school level still faces challenges because the material presented tends to be abstract, making it difficult for students to understand the concept of place value and perform addition of whole numbers. According to Piaget's theory, children aged 7 to 11 are in the concrete operational stage, thus requiring tangible media to understand abstract concepts. This aligns with Bruner's representation theory, where concrete media such as the Champion Board can help students visualize the addition process through place value columns and ice cream sticks. This study aims to describe elementary school teachers' perspectives on the effectiveness of using this media. The study uses a qualitative approach with interviews conducted with classroom teachers as the data source. Research results show that the Champion Board helps students understand place value, improve concentration, reduce calculation errors, and make the learning process more engaging. Thus, the use of concrete media is proven to be in line with students' cognitive development stages and has the potential to enhance the quality of mathematics learning.